Analysis the Effectiveness of Remdesivir, Galidesivir, Sofosbuvir, Tenofovir and Ribavirin as Potential Therapeutic Drug target against SARS-Cov-2 RNA-Dependent RNA Polymerase (RdRp): An in Silico Docking Study - Rajneesh Prajapat; Suman Jain (Journal of Research in Applied and Basic Medical Sciences, 2023)
Background & Aims:  The active site of RdRp-CoV is highly conserved, with two successive and surface-accessible aspartates in a beta-turn structure. Antiviral drugs Remdesivir, Galidesivir, Tenofovir, Sofosbuvir, and Ribavirin are known as inhibitors of RdRps, while lopinavir and rotinavir are known inhibitors of main protease (MPro) of coronavirus. The aim of the present study was to in silico test of the effectiveness of anti-polymerase drugs against SARS-CoV-2 RdRp, including 5 FDA-approved antiviral medications. Materials & Methods:  RdRp-CoV (nsp12) plays an important role in virus replication; therefore, it serves as a target to development of antiviral drugs. In this study, the RdRp is modeled, validated, and then targeted using different anti-polymerase drugs that approved for use against various viruses. Results:  The five approved drugs (Galidesivir, Remdesivir, Tenofovir, Sofosbuvir, and Ribavirin) were able to bind the SARS-CoV-2 RdRp with binding energies of 42.6, 1.7, 38.4, -1.4, and -3.9 kcal/mol, respectively. For the drug ribavirin, the only interactions established upon docking were the 11 H-bonds with F165, N459, R624, P677, N791, L460, N791, T462, N628, and T462 of the SARS-CoV-2 RdRp. Conclusion:  The results suggest the effectiveness of Ribavirin, Remdesivir, Sofosbuvir, Galidesivir, and Tenofovir as potent drugs against RdRp-CoV since they tightly bind to RdRp. The availability of FDA-approved anti-RdRp drugs can help treat the infection of new variant of SARS-CoV-2 strain specifically.